THE USE OF PROJECTS IN THE LEARNING PROCESS IN EARLY CHILDHOOD EDUCATION - Nurul Zahriani Jf; Muhd Hayyanul Damanik (Proceeding International Seminar of Islamic Studies, 2023)
This paper was created with the aim of knowing about the use of visual aids in the learning process in early childhood education. The method used is literature review with a qualitative descriptive approach. The findings show that in early childhood education, visual aids can be expressed as learning tools that are influential in advancing aspects of child development. This is because through the use of teaching aids the subject matter conveyed by the teacher can be more easily accepted by students. Teaching aids transform abstract teaching materials into concrete and realistic ones. Procurement can help students to learn more effectively and efficiently and this can certainly improve their learning outcomes. Proper and appropriate use of teaching aids helps optimize the function of all five senses in children to increase the effectiveness of children learning by hearing, seeing, feeling, and using their minds logically and realistically. Because learning is not just dreaming in abstract areas, but as a concrete empirical process that is realistic and becomes a part of life that is not easily forgotten. The use of teaching aids in learning is adjusted between the main functions of the teaching aids and the learning objectives.